Comparative Investigation on Aluminum Material Modeling with applications to Springback Prediction. Issue 1 (November 2020) - Deng, Z
Abstract: A comparative investigation on springback prediction of aluminum stampings has been completed using an industry-type "shotgun" die as the benchmark case. 5xxx aluminum alloy at a thickness of 1.5 mm was used for the shotgun die tryout. After stamping tryout, the formed panel was scanned to capture its sprung geometry. The studied aluminum alloy was characterized by means of uniaxial tensile test and hydraulic bulge test to determine the material isotropic hardening behavior and planar anisotropy. In order to determine the material kinematic hardening behavior, the exclusive Yoshida model fitting test was conducted in tension-compression (T-C) and compression-tension (C-T) loading modes with the one-cycle and three-cycle loading schemes. The shotgun benchmark case was simulated using FEA software LS-DYNA®. By comparing the simulation results with the tryout measurements, the accuracy of springback prediction was examined to evaluate the influence of material modeling, loading mode and loading cycle in the Yoshida model fitting test. Based on the current benchmark study, the best practice in springback prediction and compensation of aluminum stampings and in conducting the Yoshida model fitting test of aluminum alloys were summarized for industrial applications.